Can oral iron tablets be replaced by the intravenous iron sucrose in antenatal period? A new thought. - Tate, Snehal S.; Shirsath, Arti S.; Risbud, Neelesh S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anaemia is the commonest medical disorder that contributes significantly to maternal morbidity and mortality, preterm delivery, intrauterine growth restriction. Pregnant women are particularly vulnerable to anaemia because they have dual iron requirements both for their growth and growth of foetus. A high proportion of women in both industrialized and developing countries become anaemic during pregnancy. Intravenous iron therapy is safe convenient and effective than oral iron therapy in prevention of iron deficiency anaemia when compliance is the problem. The aim of this study is to compare the efficacy, safety and acceptability of intravenous iron Vs oral iron in prevention of iron deficiency anaemia during pregnancy. The objective of the present research was to study the efficacy, safety and acceptability of oral iron (ferrous fumarate) versus intravenous iron (iron sucrose) for the prevention of iron deficiency anaemia during pregnancy. Methods: It was a prospective comparative case control study without blinding including 400 registered antenatal women in SKNMC and GH, Narhe, Pune. Results were based on collection and analysis of data from samples within study population. Results: There was no significant difference in mean haemoglobin rise between oral group and IV group but there is significant difference between mean ferritin levels between oral group and IV group. In IV group ferritin levels at 36 weeks were almost 1.8 times more than oral group. Acceptability and convenience of IV iron was significantly more than oral iron. Conclusions: Intravenous iron therapy in the form of three divided doses, one in each trimester can be safely used in the antenatal woman as an alternative to prophylactic iron tablets for prevention of iron deficiency anaemia especially in women who are non-compliant or does not tolerate oral iron tablets.